2020
DOI: 10.1097/prs.0000000000007051
|View full text |Cite
|
Sign up to set email alerts
|

Venous Thromboembolism following Microsurgical Breast Reconstruction: A Longitudinal Analysis of 12,778 Patients

Abstract: Background: Venous thromboembolism is a dreaded complication following microsurgical breast reconstruction. Although the high-risk nature of the procedure is well known, a thorough analysis of modifiable risk factors has not been performed. The purpose of this study was to analyze the association of such factors with the postoperative occurrence of venous thromboembolism longitudinally. Methods: Using the Truven MarketScan Database, a retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Five recent publications investigate venous thromboembolism (VTE) risk reduction [1][2][3][4][5]. Rochlin et al [1] analyzed a large database and conclude that the length of hospital stay is a modifiable risk factor in microsurgical breast reconstruction patients.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Five recent publications investigate venous thromboembolism (VTE) risk reduction [1][2][3][4][5]. Rochlin et al [1] analyzed a large database and conclude that the length of hospital stay is a modifiable risk factor in microsurgical breast reconstruction patients.…”
mentioning
confidence: 99%
“…Five recent publications investigate venous thromboembolism (VTE) risk reduction [1][2][3][4][5]. Rochlin et al [1] analyzed a large database and conclude that the length of hospital stay is a modifiable risk factor in microsurgical breast reconstruction patients. However, these authors found no significant difference in VTE rates over time comparing patients treated during 2007-2009 with women treated during 2013-2015, despite the fact that patients treated during the earlier time frame had significantly longer hospital stays (4.36 days versus 4.13 days) [1].…”
mentioning
confidence: 99%
See 3 more Smart Citations